2006
DOI: 10.1063/1.2161218
|View full text |Cite
|
Sign up to set email alerts
|

An extended hindered-rotor model with incorporation of Coriolis and vibrational-rotational coupling for calculating partition functions and derived quantities

Abstract: Large-amplitude motions, particularly internal rotations, are known to affect substantially thermodynamic functions and rate constants of reactions in which flexible molecules are involved. Up to now all methods for computing the partition functions of these motions rely on the Pitzer approximation of more than 50 years ago, in which the large-amplitude motion is treated in complete independence of the other (vibrational) degrees of freedom. In this paper an extended hindered-rotor model (EHR) is developed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 40 publications
2
75
0
Order By: Relevance
“…To take thermochemical effects due to rotation of single bonds into consideration, the one-dimensional hindered rotor (1-D-HR) approach of Van Speybroeck and coworkers [38][39][40] is applied. It is well known that such a treatment significantly improves the calculated thermochemical properties, 39 in particular the entropy results.…”
Section: Hindered Rotor Treatmentmentioning
confidence: 99%
“…To take thermochemical effects due to rotation of single bonds into consideration, the one-dimensional hindered rotor (1-D-HR) approach of Van Speybroeck and coworkers [38][39][40] is applied. It is well known that such a treatment significantly improves the calculated thermochemical properties, 39 in particular the entropy results.…”
Section: Hindered Rotor Treatmentmentioning
confidence: 99%
“…While there are two other modes that might also be regarded as torsional, we did not find additional saddle points for those degrees of freedom (aside from the mirror image configurations). Multifaceted transition states have received some attention in the recent literature 55,56 and are expected to be generic for systems with energetically accessible torsional conformers. Truhlar and coworkers 57 have suggested the MS-AS method in which the contributions for the various transition state structures are summed using several possible weighting factors.…”
Section: Numerical Determination Of the State Densities Includingmentioning
confidence: 99%
“…However, it has been shown that these approximations fail when large amplitude motions are involved, 4,5 and a rigorous treatment is often required if an accurate prediction of statistical properties is required. 6−8 This is particularly the case when a torsional motion is present 7,911 or when a loose TS is involved in a dissociation/recombination reaction. 12−14 Numerous studies have been dedicated to the development of statistical methods in the context of one or the other application, while, to our knowledge, none has been presented for the general case.…”
Section: Introductionmentioning
confidence: 99%
“…12−14 Numerous studies have been dedicated to the development of statistical methods in the context of one or the other application, while, to our knowledge, none has been presented for the general case. In cases of torsional motions, the proposed treatments are usually derived from the one-dimensional hindered rotor (1DHR) model, originally proposed by Pitzer et al 4 Recent studies 7,9,11 show the importance of a rigorous treatment, where quantum effects, multidimensionality, as well as coupling with other internal or external motions can have a non-negligible influence. In the context of dissociation reactions involving a loose complex, two- to five-dimensional large amplitude motions need to be described.…”
Section: Introductionmentioning
confidence: 99%